2017
DOI: 10.3389/fimmu.2017.00265
|View full text |Cite
|
Sign up to set email alerts
|

Gastrointestinal Microbiome Dysbiosis in Infant Mice Alters Peripheral CD8+ T Cell Receptor Signaling

Abstract: We recently reported that maternal antibiotic treatment (MAT) of mice in the last days of pregnancy and during lactation dramatically alters the density and composition of the gastrointestinal microbiota of their infants. MAT infants also exhibited enhanced susceptibility to a systemic viral infection and altered adaptive immune cell activation phenotype and function. CD8+ effector T cells from MAT infants consistently demonstrate an inability to sustain interferon gamma (IFN-γ) production in vivo following va… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
24
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 31 publications
(26 citation statements)
references
References 76 publications
(74 reference statements)
1
24
1
Order By: Relevance
“…A recent study reported that maternal antibiotic treatment in mice led to significantly reduced Ag‐specific IFN‐γ production by CD8 + T cells in the mice born to these mothers after vaccinia virus infection . This effect was partially rescued by the oral administration of LPS, which suggests that the microbiota can indeed influence Ag‐specific T cell responses, although whether these effects were long‐lasting was not assessed. Similarly, the recall production of IFN‐γ or IL‐5 from Ag‐stimulated splenocytes isolated from mice immunized with HSA, and CT was completely ablated in antibiotic‐treated mice .…”
Section: T Cell Responses To Vaccinationmentioning
confidence: 99%
“…A recent study reported that maternal antibiotic treatment in mice led to significantly reduced Ag‐specific IFN‐γ production by CD8 + T cells in the mice born to these mothers after vaccinia virus infection . This effect was partially rescued by the oral administration of LPS, which suggests that the microbiota can indeed influence Ag‐specific T cell responses, although whether these effects were long‐lasting was not assessed. Similarly, the recall production of IFN‐γ or IL‐5 from Ag‐stimulated splenocytes isolated from mice immunized with HSA, and CT was completely ablated in antibiotic‐treated mice .…”
Section: T Cell Responses To Vaccinationmentioning
confidence: 99%
“…Studies investigating the impact of ABX-induced changes on GM composition and susceptibility to influenza A virus (IAV) infection in mice have focused on the impact of ABX treatment during infection of adult animals, which resulted in exacerbated disease (Ichinohe et al, 2011 ; Abt et al, 2012 ; Gonzalez-Perez et al, 2016 ; Gonzalez-Perez and Lamousé-Smith, 2017 ). Our studies have therefore focused on investigating how ABX treatment prior to, but not during, IAV infection impacts the GM composition, as well as the development of disease and immunity following subsequent IAV infection.…”
Section: Introductionmentioning
confidence: 99%
“…Tormo-Badia et al [20] observed significantly increased proportions of CD8 + T cells in the mesenteric lymph nodes (MLN) of pups born to non-obese diabetic (NOD) dams treated with antibiotics during pregnancy compared to control pups. Follow-up experiments revealed that the observed CD8 + T cell impairment was driven by an altered activation and expression of T cell receptor (TCR) critical for sustained cytokine production [22]. Follow-up experiments revealed that the observed CD8 + T cell impairment was driven by an altered activation and expression of T cell receptor (TCR) critical for sustained cytokine production [22].…”
Section: Antibiotic-induced Shifts In Microbiotamentioning
confidence: 99%
“…Similarly, pups born to mothers treated with antibiotics orally during gestation and postpartum exhibited increased susceptibility to vaccinia virus infection and reduced interferon (IFN)-γ production by CD8 + T cells when compared to controls [21]. Follow-up experiments revealed that the observed CD8 + T cell impairment was driven by an altered activation and expression of T cell receptor (TCR) critical for sustained cytokine production [22]. We recently showed, using mouse models, that altering maternal intestinal microbiota during pregnancy alone impacted inherent immunity in pups at 14 days postpartum [1] (Fig.…”
Section: Antibiotic-induced Shifts In Microbiotamentioning
confidence: 99%